Application of Coconut Shell Activated Carbon Technology for Groundwater Treatment in Roudlotut Tholibin Islamic Boarding School - Amalia FEBRIANTI; Ida MUNFARIDA; Teguh Taruna UTAMA (PT Keberlanjutan Strategis Indonesia, 2025)
Groundwater contamination poses challenges for community-based institutions, requiring effective treatment solutions. This study evaluates the efficiency of coconut shell activated carbon (CSAC) in reducing lime content in groundwater at Roudlotut Tholibin Islamic Boarding School. A seven-day filtration experiment was conducted using CSAC thicknesses of 25 cm, 35 cm, and 45 cm, with water quality assessments before and after treatment. Results showed that the 45 cm filter achieved the highest reduction, lowering lime content by 67.86%. However, one-way ANOVA and Tukey’s HSD test revealed no significant differences among the three thicknesses. Additionally, documents and policy analysis examined governance challenges in sustainable groundwater treatment. Findings identified regulatory limitations, financial constraints, and institutional capacity gaps as major barriers. While CSAC technology effectively improves groundwater quality, sustainable implementation requires stronger regulatory enforcement, financial support, and community engagement. This study highlights the potential of CSAC filtration and the need for integrated governance strategies to ensure long-term water sustainability in community-based institutions.